Lactic acidosis and the relationship with metformin usage: Case reports. Issue 46 (November 2016) - Huang, Weiyi; Castelino, Ronald L.; Peterson, Gregory M.
Abstract: Aims: The principal objective of this study was to retrospectively review a series of cases of lactic acidosis (LA) in patients with type 2 diabetes mellitus (T2DM) and examine the relationship with the use of metformin. More generally, the study enabled an investigation of the profiles of patients diagnosed with LA and clinical variables associated with in-hospital mortality. Methods: All patients admitted to the Royal Hobart Hospital in Tasmania with LA (lactate >5.0 mmol/L and pH <7.35) over a 4-year period were included. Data extracted included patient demographics, medical history, medications, acute and chronic conditions associated with LA, and relevant pathology results. Multivariate logistic regression analysis was used to identify predictors for in-hospital mortality in patients with LA. Results: A total of 139 patients with LA were included in this study. Of these, 23 patients had T2DM and 11 patients were taking metformin. All metformin-treated patients had at least 1 additional medical condition (either chronic or acute) associated with an increased risk for LA. More than half (n = 72, 51.8%) of the patients with LA died during hospitalization. Multivariate logistic regression revealed older age and lower pH as the significant independent predictors ( P < 0.05) for in-hospital mortality. Conclusion: LA was associated with high in-hospital mortality, with older age and lower pH as the significant risk factors for mortality. In patients with LA, approximately half of the patients with T2DM were receiving metformin. All the patients treated with metformin had other medical conditions that were risk factors for developing LA. The role of LA in patients treated with metformin is seemingly overemphasized.